2015
DOI: 10.1038/srep17845
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia facilitates neurogenic dural plasma protein extravasation in mice: a novel animal model for migraine pathophysiology

Abstract: Migraine animal models generally mimic the onset of attacks and acute treatment processes. A guinea pig model used the application of meta-chlorophenylpiperazine (mCPP) to trigger immediate dural plasma protein extravasation (PPE) mediated by 5-HT2B receptors. This model has predictive value for antimigraine drugs but cannot explain the delayed onset of efficacy of 5-HT2B receptor antagonists when clinically used for migraine prophylaxis. We found that mCPP failed to induce dural PPE in mice. Considering the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Regardless of the initiation site, tumor metastasis is promoted by HIF signaling; specifically, HIF-1 and HIF-2 coordinate to stabilize this pathway and maintain homeostasis of the hypoxic microenvironment[ 20 ]. As a key transcription factor, HIF-1α is involved in each step of the tumor metastatic cascade: from epithelial-mesenchymal transition (EMT)[ 7 ], intravasation[ 21 ], extravasation[ 22 ], the establishment of premetastatic niche to survival at a distant site[ 23 ]. In vitro and in vivo experiments have shown that downregulation of HIF-1α expression can significantly inhibit the malignancy phenotype of GC[ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the initiation site, tumor metastasis is promoted by HIF signaling; specifically, HIF-1 and HIF-2 coordinate to stabilize this pathway and maintain homeostasis of the hypoxic microenvironment[ 20 ]. As a key transcription factor, HIF-1α is involved in each step of the tumor metastatic cascade: from epithelial-mesenchymal transition (EMT)[ 7 ], intravasation[ 21 ], extravasation[ 22 ], the establishment of premetastatic niche to survival at a distant site[ 23 ]. In vitro and in vivo experiments have shown that downregulation of HIF-1α expression can significantly inhibit the malignancy phenotype of GC[ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pigs, selective 5-HT 2B R antagonists have been found to inhibit the 5-HT 2B R/5-HT 2C R agonist meta-chlorophenylpiperazine (mCPP) or the 5-HT 2B R agonist BW723C686-induced dural plasma protein extravasation (PPE), an indicator for migraine attacks in animal models [79]. In addition, 5-HT 2B R antagonism also prevented mCPP-induced dural PPE under hypoxia in mice [80].…”
Section: Regulation Of Pain Disordersmentioning
confidence: 99%
“…observed an mCPP-induced PPE that was associated with increased transcellular transport of dissolved substances (e.g. horseradish peroxidase, HRP) in endothelial cells with no damage of fenestrae or tight junction integrity in mice dura mater (38). Other studies showed both transcellular and para-cellular transport through the endothelial junction and clefts (39).…”
Section: The Acute Activation Of 5-ht2b Receptors Leads To Neurogenicmentioning
confidence: 99%
“…The mechanism for this shift could not be explained by an increased expression of 5-HT 2B receptors or other proteins involved. Learning more about the underlying cellular mechanisms of this phenomenon is demanding and could explain why the exclusively chronic treatment with 5-HT 2B receptor antagonists leads to a reduction of migraine attacks (38).…”
Section: The Chronic Inhibition Of 5-ht 2b Receptors May Be Prophylacmentioning
confidence: 99%